2021
DOI: 10.1021/acsami.1c19504
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzation-Triggered Ultralong Room-Temperature Phosphorescence in Biobased Nonconjugated Polymers

Abstract: Amorphous nonconjugated room-temperature phosphorescent (RTP) polymers have aroused ever-increasing attention. However, the variety of such polymers is still rare due to limited preparation strategies. Herein, we report a facile strategy to achieve ultralong RTP emission in biobased nonconjugated polymers through a hydrolyzation process. The investigated polymers are synthesized by free radical solution copolymerization using biomass methyl isoeugenol and maleic anhydride as monomers. Noticeably, the obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
(96 reference statements)
0
26
0
Order By: Relevance
“…4a), and a similar phenomenon was also observed by Deng's group. 52 Compared with PSMA-H, the phosphorescence of PSMA-Li is blue-shifted to 500 nm (Fig. 4c), influenced by ionic bonds and electrostatic interactions, and the phosphorescence lifetime reaches 39.88 ms (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…4a), and a similar phenomenon was also observed by Deng's group. 52 Compared with PSMA-H, the phosphorescence of PSMA-Li is blue-shifted to 500 nm (Fig. 4c), influenced by ionic bonds and electrostatic interactions, and the phosphorescence lifetime reaches 39.88 ms (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In our previous study, we have demonstrated that amorphous nonconjugated PMM powders prepared by radical solution polymerization could show unique blue-emitting nonconventional photoluminescence (PL) property due to the formation of emissive clusters by locked carbonyls in MAH units, following the clustering-triggered emission (CTE) mechanism. , Here, we excitingly found that the as-prepared PMM particles can also exhibit strong blue-color fluorescence emission at about 430 nm under ultraviolet excitation. More interestingly, compared with the amorphous polymer obtained by radical solution polymerization, higher PL emission intensity is observed in the PMM particles (Figure S5), together with an increase of PL quantum yield (PLQY) from 3.7% to 4.9%.…”
mentioning
confidence: 86%
“…In our previous study, 40 we have demonstrated that amorphous nonconjugated PMM powders prepared by radical solution polymerization could show unique blue-emitting nonconventional photoluminescence (PL) property due to the formation of emissive clusters by locked carbonyls in MAH units, following the clustering-triggered emission (CTE) mechanism. 28,30 Here, we excitingly found that the as-prepared PMM particles can also exhibit strong blue-color fluorescence emission at about 430 nm under ultraviolet excitation.…”
mentioning
confidence: 99%
“…In general, the challenge to generate RTP for organic chromophores lies in the insufficient intersystem crossing (ISC) caused by weak spin-orbit coupling (SOC), ultrafast nonradiative decays, and oxygen quenching. A variety of strategies have been proposed to promote ISC processes by inclusion of heavyand/or hetero-atoms 20,27,28 and deuteration, 29,30 and to suppress nonradiative relaxations using crystal engineering, [31][32][33][34][35] host-guest doping, 2,7,36 crosslinking, 37 polymerization [38][39][40][41] and many other methods. As a result, a growing number of organic RTP materials with long-lived lifetimes (4100 ms) under ambient conditions have been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%